MEAN PLATELET VOLUME DI STROK - Besse Rosmiati; Sulina Y Wibawa; Darmawaty ER (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2012)
Ischemic stroke is the cause of most cases which occur due to obstruction, this pathogenesis can be caused by the formation of thrombus in the cerebrum blood vessels. Platelet aggregation plays a role in the pathogenesis of thromboembolic cerebrovascular disease. Platelets size, measured as Mean Platelet Volume (MPV) is a marker of platelet function and is associated with the indicator of platelet activity. Several studies have found that there was an increased of MPV in acute ischemic stroke while the correlation with the severity and outcome of stroke was still controversial. The aim of study is to determine the MPV and their association with outcomes in acute ischemic stroke patients. A cohort study during May up to July 2010 was carried out, the researchers measured MPV and analyze their correlation with its outcome using modified Rankin scale score 10 days after the onset in 33 acute ischemic stroke patients. The mean of MPV for the first three days of the onset was 8.9 fl, on the 5th day was increased up to 9.4 but at the 10th day of onset the MPV remains the same value as the 5th day. The MPV of first three days and 5th day have a positive correlation, but insignificant with their outcome, with p values 0.158 and 0.06, respectively. From this study can be concluded that the increased of MPV on the fifth day onset did not have any significant correlation with the outcome of acute ischemic stroke illness.